Modernizing Pesantren Educational Management: Strategies for Sustainable Quality Improvement - Rina Yunita Maulida; Mahbubil Maula Azfa (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2026)
This study explores the modernization of educational management in Islamic boarding schools (pesantren) as a strategic approach to sustainable quality improvement. Pesantren, as Indonesia's oldest Islamic educational institutions, face the challenge of integrating deeply rooted traditional values with the demands of contemporary educational management. Employing a qualitative case study design, data were collected from three purposively selected pesantren in Central and East Java through in-depth interviews with twelve key informants including kyai/heads, daily administrators, ustadz/ustadzah, and senior santri complemented by participatory observation over a three-month period at each site and systematic documentation review. The findings reveal that modernization of pesantren educational management encompasses four strategic dimensions: (1) leadership transformation from charismatic-personal toward spiritual-professional-managerial models; (2) integrative curriculum development that proportionately balances religious knowledge (ilmu naqli) with general knowledge (ilmu aqli); (3) upgrading of facilities and infrastructure to support controlled digital learning; and (4) systematic implementation of data-driven management functions planning, organizing, actuating, and controlling grounded in accountability. The study concludes that successful modernization requires balancing tradition preservation with adaptive innovation, fostering broad stakeholder participation, and investing in continuous human resource development. Theoretically, this research contributes a Tradition, Modernity, CQI Synthesis Model grounded in Kotter's change management theory, transformational leadership theory, and the continuous quality improvement (CQI) framework, demonstrating that pesantren modernization is not the replacement of tradition with secular managerial logic, but rather the strengthening of Islamic authenticity through adaptive institutional innovation.